2019
DOI: 10.1111/2041-210x.13281
|View full text |Cite
|
Sign up to set email alerts
|

CORIGAN: Assessing multiple species and interactions within images

Abstract: Images are resourceful data for ecologists and can provide a more complete information than other methods to study biodiversity and the interactions between species. Automated image analysis however often relies on extensive datasets, not implementable by small research teams. We are here proposing an object detection method that allows the analysis of high‐resolution images containing many animals interacting in a small dataset. We developed an image analysis pipeline named ‘CORIGAN’ to extract the characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Poeydebat et al (2017) found a negative correlation between generalist predator abundance and C. sordidus abundance. In Costa Rica, cockroaches have been observed to feed on exposed C. sordidus larvae (Tresson, Tixier, Puech, Bagny Beilhe, et al, 2019). Vinatier et al (2009) also emphasized the effect of predators on the developmental stages of C. sordidus; the authors indicated that generalist predators and particularly egg predators help reduce banana weevil numbers.…”
Section: Generalist Arthropod Predatorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Poeydebat et al (2017) found a negative correlation between generalist predator abundance and C. sordidus abundance. In Costa Rica, cockroaches have been observed to feed on exposed C. sordidus larvae (Tresson, Tixier, Puech, Bagny Beilhe, et al, 2019). Vinatier et al (2009) also emphasized the effect of predators on the developmental stages of C. sordidus; the authors indicated that generalist predators and particularly egg predators help reduce banana weevil numbers.…”
Section: Generalist Arthropod Predatorsmentioning
confidence: 99%
“…Photographs taken in the field allowed detailed analysis of the behaviours of different ant species in Costa Rica (Tresson, Tixier, Puech, Bagny Beilhe, et al, 2019). Camponotus atriceps (Hymenoptera, Formicinae) were observed to feed on dead adults but not on any living stages of C. sordidus; S. geminata consumed C. sordidus eggs and larvae but were unable to kill a live adult; Pheidole radoszkowskii (Hymenoptera, Myrmicinae), O. bauri and Nylanderia sp.…”
Section: Special Case Of Antsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent uses include for example species detection and tracking [ 25 ] or interaction analysis [ 26 ]. The use of automated image analysis can allow a detailed study of the recruiting dynamics of ants or of the number of individuals needed to seize a prey animal, enabling the reconstruction of the observed interaction network [ 26 ]. In some cases, however, image analysis can be performed with less demanding methods, such as background subtraction or color thresholding, and yield sufficient results without the need of a specific labelled dataset.…”
Section: Introductionmentioning
confidence: 99%